Seeing the myth in human rights - Reinbold, Jenna (Pennsylvania studies in human rights, 2017)
Seeing the Myth in Human Rights explores the role of myth in the creation and propagation of the 1948 Universal Declaration of Human Rights. Drawing on records, publications, and speeches from the Declaration's creators as well as current scholarship on human rights, Jenna Reinbold sees the Declaration as an exemplar of modern mythmaking.